Tracing the trails in the medieval world : epistemological explorations, orientation, and mapping in medieval literature - Classen, Albrecht (New York: Routledge, 2021)
"Only a highly comparative study of medieval literature can help us to comprehend how much fundamental ideas and concepts were shared throughout the entire period. The idea of the trail as an epistemological vehicle for the protagonists proves to be critical in reaching a deep understanding of medieval values and ideals"--
Includes bibliographical references and index.
Keywords: Literature, Medieval -- History and criticism; Trails in literature; Space and time in literature; Knowledge, Theory of, in literature